Fracture patterns and causes in the craniofacial region: an 8-year review of 2076 patients - Ki-Su Jin; Ho Lee; Jun-Bae Sohn; Yoon-Sic Han; Da-Un Jung; Hye-Young Sim; Hee-Sun Kim (SpringerOpen, 2018)
Abstract Background For proper recovery from craniofacial fracture, it is necessary to establish guidelines based on trends. This study aimed to analyze the patterns and causes of craniofacial fractures. Methods This retrospective study analyzed patients who underwent surgery for craniofacial fractures between 2010 and 2017 at a single center. Several parameters, including time of injury, region and cause of fracture, alcohol intoxication, time from injury to surgery, hospitalization period, and postoperative complications, were evaluated. Results This study analyzed 2708 fracture lesions of 2076 patients, among whom males aged 10 to 39 years were the most numerous. The number of patients was significantly higher in the middle of a month. The most common fractures were a nasal bone fracture. The most common causes of fracture were ground accidents and personal assault, which tended to frequently cause more nasal bone fracture than other fractures. Traffic accidents and high falls tended to cause zygomatic arch and maxillary wall fractures more frequently. Postoperative complications-observed in 126 patients-had a significant relationship with the end of a month, mandible or panfacial fracture, and traffic accidents. Conclusions The present findings on long-term craniofacial fracture trends should be considered by clinicians dealing with fractures and could be useful for policy decisions.